First-principles calculation of structural, optoelectronic properties of the cubic AlxGayIn1-x-y N quaternary alloys matching on AlN substrate, within modified Becke–Johnson (mBJ) exchange potential - Amina, B.; Lachebi, A.; Shuhaimi, A.; Rahman, S.A.; Abid, H. (Elsevier, 2016)
A theoretical study of zinc-blende quaternary alloys AlxGayIn1-x-y N (x = 0.343, 0.468, 0.593 and y = 0.375, 0.5, 0.625) grown on AlN substrate where the lattice match condition is 〈ABS−P〉y=1,25(1−x). The full-potential linearized augmented plane wave method (FP-LAPW) was used to determine the variations in the bandgap as well as the optical properties. The generalized gradient approximation of Wu and Cohen (WC-GGA) was employed for the exchange-correlation potential to calculate the structural properties and the modified Becke–Johnson potential (TB-mBJ) employed for greater generation of the band gap and the optical properties. The structural properties (lattice parameters and bulk modulus) were assessed for binary, ternary and quaternary compounds. Whenever possible, results were compared with experiments and calculations completed with other computational schemes. The theoretical study of the optoelectronic properties demonstrate that these materials are applicable for optical device working in UV spectrum.